Analisis Pengendalian Internal atas Penjualan Tiket Kapal dalam Bukti Penerimaan Kas PT Pelni Cabang Surabaya (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of the business world encourages companies to adopt automation and efficiency. PT Pelni Cabang Surabaya, as a provider of sea transportation services, relies on an accounting system for recording service revenue. This study analyzes the effectiveness of internal control over recording ticket sales in accordance with the components of the COSO Framework (2013) including ticket cancellations in cash receipts. The method used is descriptive qualitative with a case study approach. The results of the study indicate that the assessment of the COSO components has been adequate even though PT Pelni has implemented several elements of internal control, there are still weaknesses in the verification of canceled ticket transactions that pose a risk to the accuracy of financial records. This study emphasizes the importance of strengthening supervision and recording systems to support financial accountability.